2013
DOI: 10.1007/s00018-013-1471-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ubiquitin–proteasome system in the regulation of P2Y13 receptor expression: impact on hepatic HDL uptake

Abstract: The protective effect of high density lipoproteins (HDL) against atherosclerosis is mainly attributed to their capacity to transport excess cholesterol from peripheral tissues back to the liver for further elimination into the bile, a process called reverse cholesterol transport (RCT). Recently, the importance of the P2Y13 receptor (P2Y13-R) was highlighted in HDL metabolism since HDL uptake by the liver was decreased in P2Y13-R deficient mice, which translated into impaired RCT. Here, we investigated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Ubiquitination at its C-terminal end leads to proteasomal degradation and poor surface expression (Pons et al, 2014). However its surface expression increases in response to oxidative stress and genotoxins such as cisplatin or UV irradiation (Morente et al, 2014).…”
Section: P2 Receptors Determine the Eventual Effect Of Extracellular Atpmentioning
confidence: 99%
“…Ubiquitination at its C-terminal end leads to proteasomal degradation and poor surface expression (Pons et al, 2014). However its surface expression increases in response to oxidative stress and genotoxins such as cisplatin or UV irradiation (Morente et al, 2014).…”
Section: P2 Receptors Determine the Eventual Effect Of Extracellular Atpmentioning
confidence: 99%
“…Haynes et al () and Stefani et al () found that, despite confirming P2Y 13 mRNA expression in microglia (Zhang et al, ), its expression could not be detected at the protein level. The inability to antibody‐label P2Y 13 may reflect a high rate of constitutive proteasomal degradation (Pons et al, ), or may alternatively suggest that P2Y 13 protein is only expressed at high levels in microglial culture (Quintas, Vale, Goncalves, & Queiroz, ) or upon microglial activation in situ (Niu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, almost all of these studies relied highly upon the use of MRS 2211 to block P2Y 13 receptors, but we have now shown this is not a selective P2Y 13 antagonist. Furthermore, the failure, to date, to demonstrate microglial P2Y 13 protein expression in vivo suggests either that the commercially available P2Y 13 antibodies lack specificity or that the constitutive proteasomal degradation of the receptor shown to regulate the surface expression of the receptor in hepatocytes (Pons et al, ) also happens in microglia in vivo (which would imply that a low level of surface receptors can still have a significant effect on cell function).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations